Health monitoring IoT device with risk prediction using cloud computing and machine learning - Das, Anindya; Nayeem, Zannatun; Faysal, Abu Saleh; Himu, Fardoush Hassan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.